Effect of pre-treatment and calcination temperature on Al2O3-ZrO2 supported Ni-Co catalysts for dry reforming of methane. (13th August 2019) - Al-Fatesh, Ahmed Sadeq; Abu-Dahrieh, Jehad K.; Atia, Hanan; Armbruster, Udo; Ibrahim, Ahmed A.; Khan, Wasim U.; Abasaeed, Ahmed Elhag; Fakeeha, Anis H.
Abstract: In this paper, the effect of pre-treatment and calcination temperature on a series of 5%Co/Al2 O3 -ZrO2, 5%Ni/Al2 O3 -ZrO2 and 2.5%Co-2.5%Ni/Al2 O3 -ZrO2 catalysts for dry reforming of methane was investigated. Main focus of our research was to improve the catalyst stability by proper pre-treatment and reaction conditions. The first approach aimed at the catalyst pre-treatment by using bimetallic systems and the second strategy at the in situ suppression of coke. The catalytic activity of bimetallic system was indeed higher compared to the monometallic in the temperature range of 500–800 °C (space velocity 18000 ml h −1 ·gcat −1, CH4 /CO2 = 1). The bimetallic catalyst calcined at 800 °C showed highest CH4 conversion without deactivation and gave a H2 /CO ratio of 91% and 0.96, respectively, and good stability with less coke deposition over 28 h at 800 °C reaction temperature. This improvement is assigned to the synergism between Co and Ni, their high dispersion according to interaction with support. It has been shown in our work that pretreatment temperatures and atmospheres have strong impact on stability of the catalyst. TEM, XRD and TPO investigations confirmed that the slight catalyst deactivation was related to the formation of multiwall carbon nanotubes with hollow inner tube structure. The addition of small amounts of steam or oxygen during DRM improved both the catalyst activity and stability as the bimetallic catalyst lost around 9.4% conversion in DRM, 5.4% in presence of water and only 3.2% in presence of O2 . Highlights: 2.5%Co-2.5%Ni/Al2 O3 -ZrO2 catalyst calcined at 800 °C showed higher activity. 2.5%Co-2.5%Ni/Al2 O3 -ZrO2 had less coke deposition for 28 h reaction time. The CoNi-4 catalyst is capable of operating under different feed compositions. CoNi-4 catalyst activity is improved by addition of small amount of steam or O2 .